Nutrient recovery from biomass cultivated as catch crop for removing accumulated fertilizer in farm soil - Nagare, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
As a result of long-term continuous use of fertilizers in farm land, a large amount of nutrients accumulate in the soil, increasing the risk of eutrophication or nitrate pollution of groundwater. For rehabilitating the farm soil and recovering nutrients such as nitrogen, phosphorus and potassium, a new system has been developed by our research group. This paper discusses the methodology of extracting nutrients from biomass in order to recover phosphorus and other nutrients in crystal form. Around 80% or higher extraction rates were achieved for phosphorus and potassium by soaking the powdered tissue in distilled water or 1% NaOH solution for 24 h. The extracted phosphorus and potassium act as a potential resource for recycled fertilizer or other industrial materials